Introduction to plant physiology - William G Hopkins (John Wiley, 1995)
The book assemles and explains, in a narrative format, underlying concepts of plant physiology within a framework of historical origins and modern approaches. It covers the water relations of plants and plant cells, and the acquisition of inorganic nutrients; deals with energy transduction and carbon metabolism, including the distribution of carbon in the phloem; also covers the regulation of plant development; and deals with the physiology of plants under stress and, by way the pointing toward the future, concludes with a discussion of plant physiology and technology